Pengaruh Pengolahan pada Sifat Fisis dan Kimia Singkong-Goreng Beku - Tiara Indra Saraswati; Dede Robiatul Adawiyah; Fransisca Zakaria Rungkat (Jurnal Ilmu Pertanian Indonesia, 2022)
Cassava (Manihot esculenta) can be used as the main source of carbohydrates besides rice. Although cassava has been widely used, the diversification of cassava islimited. Appropriate processing methods are needed so that the nutrition value of cassava can be maintained and safe for consumption. This study aimed to evaluate the nutrition value of frozen cassava fries through proximate, minerals, cyanide content, and trans fatty acids analysis and to assess the physical quality, such as color and texture. The best-frozen cassava fries processing methods obtained were steaming 100°C for 25 minutes and deep frying 180°C for 45 seconds. The results showed that color analysis L (tingkat kecerahan), a* (koordinat kromatisitas), and b* (koordinat kromatisitas), were 70.39±0.98, -2.11±0.72, and 28.06±1.06. The levels of protein, fat, and carbohydrates were 1.14±0.271 g/100g, 12.18±0.017 g/100g, dan 35.80±0.023 g/100g. The levels of Ca, Mg, and Fe were 274.047±7.42 mg/100g, 17.3±0.31 mg/100g, dan 4.59±0.26 mg/100g. The cyanide level decreased to 2.602±0.00 mg/kg from 75.458±0.00 mg/kg. In all frying treatments, trans fatty acids were not detected. In conclusion, frozen cassava fries have potential as a healthy diet component. Keywords: cassava, deep frying, frozen-fried cassava